Significance of Selected Halocarbons Monitoring in Air Samples Collected in the Terra Nova Bay region (northern Victoria Land, Antarctica) - MANGANI, FILIPPO; MAIONE, MICHELA; LATTANZI, LUCIANO (Antarctic Science, 1999)
CCl3F (or CFC-11) and CCl2F2 (or CFC-12) were determined in air samples collected, during subsequent summer Antarctic campaigns, in different sampling sites in the Ross Sea Region. The samples were analysed by GC-ECD after enrichment. Data obtained since 1988–89 were plotted to observe the trend of CFCs atmospheric concentration levels. A decrease in the rate of increase of CFC-12 concentration was observed, whilst the concentration of CFC-11 was actually seen to be decreasing.